1964
DOI: 10.1039/jr9640002051
|View full text |Cite
|
Sign up to set email alerts
|

389. Topochemistry. Part VII. The photoactivity of anils of salicylaldehydes in rigid solutions

Abstract: By M. D. COHEN, (the late) Y. HIRSHEERG, and G. M. J. SCHMIDT. All anils of salicylaldehydes investigated undergo colour changes whenThe In some solvents the change their solutions in rigid glasses are irradiated with ultraviolet light. effect is reversed when the solutions soften. can be reversed photochemically even while rigidity is maintained.Anils of aldehydes lacking an o-hydroxyl group show no photoactivity.PART VI * has discussed experimental work on the photoactivity of solid salicylideneanilines. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…[25] In all three cases of o-hydroxy imines reported here, the dihedral angles between aromatic subunits are well under 25° (Table 1), the value which has been declared in literature and several times disproved as an important criterion for thermochromic behaviour. [12][13][14][15][16][17][18][19][20][21][22][23] A molecular overlay of molecules of all three Schiff bases is given in Figure 3b and shows the small deviation of the molecules from planarity. The influence of temperature on the planarity of these three imines is neglectable.…”
Section: Csd [24] Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[25] In all three cases of o-hydroxy imines reported here, the dihedral angles between aromatic subunits are well under 25° (Table 1), the value which has been declared in literature and several times disproved as an important criterion for thermochromic behaviour. [12][13][14][15][16][17][18][19][20][21][22][23] A molecular overlay of molecules of all three Schiff bases is given in Figure 3b and shows the small deviation of the molecules from planarity. The influence of temperature on the planarity of these three imines is neglectable.…”
Section: Csd [24] Data Analysismentioning
confidence: 99%
“…[11] The microscopic reasons of such macroscopic properties are still under investigation, [7,8,[12][13][14][15][16][17][18][19] and this work is one of them. There are three described mutually dependant reasons for such behaviour in the solid state: proton transfer via intramolecular O⋯N hydrogen bonds and thus the change of the tautomeric form, [12][13][14][15][16][17] the contribution of fluorescence and not only of light absorption as a consequence of the tautomeric change and the change in molecular geometry. [18] The scientists are still trying to either reaffirm the mentioned reasons or to find imines in which the reasons cannot be strictly determined but they do show such chromic change.…”
Section: Introductionmentioning
confidence: 99%
“…Cohen et a/. (5,6) report the spectra of irradiated and nonirradiated low temperature solutions of several N-salicylideneanilines and in all cases it appears that the increase in absorbance at the visible wavelength is greater than the decrease in absorbance at the near ultraviolet wavelength. In no case, however, is the ratio so large as in the case of the ultrathin polycrystalline film reported here.…”
Section: A Ultraviolet-visible 1neasllrelnetztsmentioning
confidence: 99%
“…One equilibrium involves proton transfer and tautomerization and the other involves a trans + cis isomerization about the central carbon-nitrogen double bond. Other authors (5,6,22) have also suggested that more than three molecular species may be involved in these processes. Hadjoudis et a / .…”
Section: Introductionmentioning
confidence: 99%
“…N-substituted imines can be easily synthesized by condensation of aldehydes (or ketones) and primary amines [12] and used not only for the investigation of their physico-chemical properties, but also because of their well-recognized biological and pharmacological properties [9,[13][14][15][16], as well as their metal complexes [17]. There are three mutually-dependent reasons for such behavior in the solid state described in the literature: (a) proton transfer via intramolecular O···N hydrogen bonds and thus (b) the change of the tautomeric form [18][19][20][21][22][23] and (c) the contribution of fluorescence and not only of light absorption as a consequence of the tautomeric change and the change in molecular geometry [24]. Another intriguing "well-known fact" about thermo-and/or photochromism of o-hydroxy Schiff bases is that these two phenomena are mutually exclusive and that imines with planar molecules light absorption as a consequence of the tautomeric change and the change in molecular geometry [24].…”
Section: Introductionmentioning
confidence: 99%